المشاركة الوالدية في فعالية برنامج التدخل المبكر بذوي متلازمة داون - بن طالب, غنية; فنطازي, كريمة (جامعة الوادي - University of Eloued, 2023)
هدفت الدراسة الحالية إلى الكشف عن مدى اسهام المشاركة الوالدية في فعالية برنامج التدخل المبكر بذوي متلازمة داون من وجهة نظر المختصين والوالدين في مراكز الأطفال المعاقين ذهنيا بمدينة عنابة. واستخدمت الباحثتان المنهج الوصفي المسحي من خلال بناء أداة الدراسة (الاستبيان)، حيث تكونت عينة الدراسة من (32) مختص وفق متغير سنوات الخدمة، و(29) من أولياء الأطفال ذوي متلازمة داون وفق متغير المستوى التعليمي، في المراكز النفسية البيداغوجية بمدينة عنابة. وتحقق الباحثان من فرضيات الدراسة باستخدام الأسلوب الإحصائي المناسب (ك²)، وأظهرت النتائج أن متغير سنوات الخدمة ومتغير المستوى التعليمي لم يؤثرا في آراء أفراد العينة الذين اتفقوا حول عدم اسهام المشاركة الوالدية في فعالية برنامج التدخل الوقائي والتدخل العلاجي والتدخل التربوي. The current study aimed to reveal the extent to which parental participation contributed to the effectiveness of the early intervention program for people with Down syndrome from the point of view of specialists and parents in the centers of mentally handicapped children (Annaba). The two researchers used the descriptive survey method by building the study tool (the questionnaire), and the study sample consisted of (32) specialists according to the variable years of service and (29) parents of children with Down syndrome according to the variable of educational level, then the study hypotheses were verified using the appropriate statistical method (K²). The results showed that the years of service variable and the educational level variable did not affect the opinions of the sample members who agreed that parental participation did not contribute to the effectiveness of the preventive intervention program, the therapeutic intervention and the educational intervention.
Parental participation in the effectiveness of the early intervention program for Children with Down syndrome
مقال
Keywords: مشاركة الأولياء ، برنامج التدخل المبكر ، ذوي متلازمة داون; parental participation , early intervention program , Children with Down syndrome